The wave of consent-based rape laws in Europe - Uhnoo, Sara (International journal of law, crime and justice, 2024)
After years of feminist struggle, international conventions, and the #MeToo movement, consent-based rape laws have rapidly been replacing coercion-based laws across Europe since 2017. In May 2023, we identified 20 European consent-based rape laws, and more were in progress. This article analyses the emergence and convergence of these laws, drawing on the theory of institutional isomorphism. The analysis is based on a collection of criminal codes, draft laws, news articles, previous research, and input from national experts. We map a timeline of consent-based rape laws in Europe and describe their key elements, identifying patterns such as international pressure, influential countries, civil society impact, and cases of sexual violence triggering national debates preceding legislative changes.